Limites e potencialidades da formação e atuação em rede de cooperativas de catadore(a)s de materiais recicláveis: caso da Rede Anastácia, estado de São Paulo - Soares, Alexandra Savio (2017)
The work carried out by recyclable waste pickers is of great importance, not only for the reuse of the materials, but also for their benefit to the environment, reducing the amount of waste that goes to landfills and landfills. Despite the significant work done by the collectors, it is verified that in the recycling chain these are the least benefited. The reasons for this are diverse, such as the organizational and infrastructure precariousness of the enterprises, the lack of support and recognition for the service provided to society, the action of the intermediaries who buy the materials at very low prices, among others. In order to improve the participation of the collectors in the recycling chain, some initiatives are being taken, such as the formation of cooperation networks of solid economic enterprises, which among the objectives is to strengthen the way of work and performance of the collectors. Based on this idea, Rede Anastácia was created in the central region of the state of São Paulo and Alta Mogiana, which is a regional network of collectors of recyclable materials that counts on the participation of eight cooperatives located in different municipalities of the state. In this way, a research was conducted with the Rede Anastácia, from May / 2015 to October / 2016, which used the exploratory method, with direct observation of a qualitative approach, through a visit to cooperatives, photographic records, analyzes Of documents, participation in meetings and activities, in order to identify and evaluate the limits and potentialities of the formation and operation of cooperation networks. As results, information on cooperative characteristics, creation and formalization of the network, its main articulations (meetings and activities) to strengthen cooperatives, the expectations of the collectors to belong to the network and the main limits and potentialities were obtained. Among the limitations identified are the need for improvements in the infrastructure of cooperatives; The distance between them and the lack of standardization in the types of materials sorted and detailed record on productivity, which ends up hampering joint marketing actions. As potentialities: there was an increase in the exchange of information among cooperatives; Greater possibility of participation in projects of technical and financial incentive; Greater political representativeness; Conducting joint sales; Participation in reverse logistics systems, among others. Regarding the collectors' expectations of belonging to the network, it was verified that they believe that there may be an improvement in the valorization and recognition of the work done by the collector, greater possibility of realizing joint marketing and verticalization of materials, among other aspects.